Intercropping of different vegetables and field spices with brinjal (Solanum melongena) - Prasad, K S; Mohan, N K (The Indian Journal of Agricultural Sciences, 2012)
A 2 year field experiment was conducted during winter season of 1991-92 and 1992--93 to study the performance of brinjal (Solallum melollgena L.) as a main crop and its intercropping with 'Pusa Desi' radish (Raphanus salivus L.), 'Pusa Parvati' french bean (Phaseolus vulgaris L), 'White Vienna' knolkohl (Brassica oleracea L. var gongylodes L.), ‘Methi 47' fenugreek (Trigermala foenum- graecum L.) and local coriander (Coriandrum salivum L.). The highest yield of brinjal (16.23 (onnes/ha) was recorded in the monocrop (brinjal alone), followed by brinjal + french bean (16.08 tonnes/ha). In terms of benefit; cost ratio, brinjal + french bean intercropping was most remunerative (1.99).